The one-step synthesis and surface functionalization of dumbbell-like gold–iron oxide nanoparticles: a chitosan-based nanotheranostic system. Issue 2 (2nd November 2015) - Kostevsek, Nina; Locatelli, Erica; Garrovo, Chiara; Arena, Francesca; Monaco, Ilaria; Nikolov, Ivaylo Petrov; Sturm, Saso; Zuzek Rozman, Kristina; Lorusso, Vito; Giustetto, Pierangela; Bardini, Paola; Biffi, Stefania; et al.
Abstract : The first one-step synthesis of dumbbell-like gold–iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool. Abstract : The first one-step synthesis of dumbbell-like gold–iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool.